THE TYPES OF RESOURCEFULNESS ORIENTATION OF A PERSON - Shtepa, Olena (Psychological Prospects Journal, 2015)
While characterizing the notion of resource scholars most frequently reveal its essence through notions of potential, ability, reserve and chance. For a better definition of correlation between notions of resource and potential, ability, reserve, and chance, we suggest distinguishing the criteria of resource. The main aspects of resource may be defined as self-determination of a person in relationships and humanistic attitude towards others. Distinguished aspects of resource are analogous to directions in which personal orientation is defined. Based on the data of multi-factor and cluster analysis, as well as on the method of principal components, the types of psychological resourcefulness have been established: (the manner of appropriateness of allocation of the following resourcefulness types has been empirically grounded) «resource as an ability», «resource as a potentiality», «resource as a reserve», «resource as a chance». It has been established that the principal components of psychological resourcefulness characterize the following personal-existential resources: «helping others», «kindness to people», «belief in good», «pursuit of wisdom». It has been determined that the main factors of psychological resourcefulness are the knowledge of a person’s own resources and the ability to renovate and use these resources, as well as individual-existential resources «belief in good» and «helping others». The results of the empirical research have allowed identifying the types of psychological resourcefulness in vectors of the types «actualization» and «actualizing the resourcesof self-development».